Constructing the Purposes of Punishment in the National Criminal Code: Weaving a Prophetic Basis for Transcendent Justice - Sahran Hadziq; Muhamad Syamsudin; Aroma Elmina Martha (Universitas Muhammadiyah Purwokerto, 2026)
The reform of the criminal law in Indonesia through Law Number 1 of 2023 concerning the National Criminal Code (National Criminal Code) has marked a fundamental paradigm shift, especially related to the expansion of the principle of legality and the formulation of penal objectives. This shift indicates the inclusion of